Detecting Underground Military Structures Using Field Spectroscopy - Melillos, George; Themistocleous, Kyriacos; Agapiou, Athos; Michaelides, Silas; Hadjimitsis, Diofantos G. (My University, 2019)
Satellite remote sensing is considered as an increasingly important technology for detecting underground structures. It can be applied to a wide range of applications, as shown by various researchers. However, there is a great need to integrate information from a variety of sources, sent at different times and of different qualities using remote sensing tools. A SVC-HR1024 field spectroradiometer could be used, and in-band reflectance’s are determined for medium- and highresolution satellite sensors, including Landsat. Areas covered by natural soil where underground structures are present or absent can easily be detected, as a result of the change in the spectral signature of the vegetation throughout the phenological stages; in this respect, vegetation indices (VIs) such as the normalized difference vegetation index (NDVI), simple ratio (SR), and enhanced vegetation index (EVI) may be used for this purpose. Notably, the SR vegetation index is useful for determining areas where military underground structures are present.
Keywords: Spectroscopy; Military underground structures; Vegetation indices; Landsat